1997
DOI: 10.1021/la960430w
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Electrochemical Removal and Efficient Re-formation of a Monolayer of Hexadecanethiol Self-Assembled at an Au(111) Single Crystal in Aqueous Solutions

Abstract: The electrochemistry of a hexadecanethiol monolayer deposited on a Au(111) single crystal electrode has been examined in electrolyte solutions of different pH values, and it has been found that a significant fraction of the hexadecanethiol monolayer can be electrochemically removed and redeposited repetitively from the Au(111) surface. We suggest that this behavior is caused by the low solubility of the reduced molecules which prevents their diffusion into the bulk of the solution. The solubility of the thiol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
236
1
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(266 citation statements)
references
References 36 publications
26
236
1
3
Order By: Relevance
“…They are 54.9, 57.5, 58.9, 63.0 and 65.1 µC cm -2 in 10 µM, 50 µM, 100 µM, 500 µM and 1 mM thiol solutions, respectively, and are smaller than 73.3 µC cm -2 , which is the expected value for the saturated coverage, i.e., (√3 x √3)R30° structure [44][45][46][47][48]. The value of 73.3 µC cm -2 has been reported for the reductive desorption of the SAM formed externally in an ethanol solution containing only the thiol [23,24].…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…They are 54.9, 57.5, 58.9, 63.0 and 65.1 µC cm -2 in 10 µM, 50 µM, 100 µM, 500 µM and 1 mM thiol solutions, respectively, and are smaller than 73.3 µC cm -2 , which is the expected value for the saturated coverage, i.e., (√3 x √3)R30° structure [44][45][46][47][48]. The value of 73.3 µC cm -2 has been reported for the reductive desorption of the SAM formed externally in an ethanol solution containing only the thiol [23,24].…”
Section: Introductionmentioning
confidence: 68%
“…Au -SR + e -=> Au + RS - (1) many electrochemical studies of the reaction (1) have been carried out because the peak area and the shape of the cathodic peak for the reductive desorption and its peak potential provide useful information of the SAM such as the adsorbed amount, stability, adsorption energy, orientation, and substrate morphology [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. For example, it was found that the longer the alkylchain, the more negative the reductive peak potential, reflecting the stronger van der Waals attractive interaction among alkylchains [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this annealing procedure, the vacancies and step edges move by diffusion of single substrate atom vacancies [26,45]. This [74,75], demonstrating that they bind strongly; below -500 mV sulphide desorbs from Au(lll) [7]; below -300 mV iodide desorbs from Pt(110), causing surface mass transport of the substrate [72]; -200 mV suffice to desorb the weaker bonded sulphate ion from platinum surfaces [76]). In the positive potential range, the situation can be much more complex; often an adsórbate is first oxidized and the product can desorb, e.g.…”
Section: Thiolate Layers and The Electrodeposition Of Metalsmentioning
confidence: 99%
“…4 In other studies by Morin and coworkers, the amount oxidatively re-deposited was affected by the pH of the solution. 5,6 It was suggested that the amount of the redeposition by the oxidation decreases with the increasing solubility of the thiols because of the diffusion into the bulk of the solution.For this study, 2-aminoethanethiol (HSCH 2 CH 2 NH 3 + ) in a pH 6 aqueous solution, which has not been studied for the reductive desorption reaction, was used as a thiol compound. It has a short chain length with an ionic amino group and is easily dissolved in an aqueous solution.…”
mentioning
confidence: 99%